2011
DOI: 10.1021/ja2077922
|View full text |Cite
|
Sign up to set email alerts
|

Selective Uncoupling of Individual Mitochondria within a Cell Using a Mitochondria-Targeted Photoactivated Protonophore

Abstract: Depolarization of an individual mitochondrion or small clusters of mitochondria within cells has been achieved using a photoactivatable probe. The probe is targeted to the matrix of the mitochondrion by an alkyltriphenylphosphonium lipophilic cation and releases the protonophore 2,4-dinitrophenol locally in predetermined regions in response to directed irradiation with UV light via a local photolysis system. This also provides a proof of principle for the general temporally and spatially controlled release of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 38 publications
0
102
0
2
Order By: Relevance
“…However, 2,4-DNP's narrow therapeutic window led to the abandonment of its use. A recent study found that 2,4-DNP linked to TPP in a covalent manner is ineffective at uncoupling (30). Concerns about the narrow therapeutic window and failure of the covalently linked uncoupler have led to the evaluation of mitochondria-targeted NPs in directing this uncoupler to the mitochondria of cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, 2,4-DNP's narrow therapeutic window led to the abandonment of its use. A recent study found that 2,4-DNP linked to TPP in a covalent manner is ineffective at uncoupling (30). Concerns about the narrow therapeutic window and failure of the covalently linked uncoupler have led to the evaluation of mitochondria-targeted NPs in directing this uncoupler to the mitochondria of cells.…”
Section: Resultsmentioning
confidence: 99%
“…For uncouplers to work safely, these compounds should cause uncoupling that increases very little as their concentration rises, potentially widening the difference between therapeutic and toxic doses and giving a wide therapeutic window (62). Recently, however, targeted uncoupling showing precise spatial and temporal control of mitochondrial function have been demonstrated, leading to the selective uncoupling of either individual or small groups of them within a cell (63,64). Such technology, if adapted to SR4 in the future, will increase its safety and potentially lower the effective maximum dose required for its cytotoxic effects on tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques to study how mitochondria control specific signals are improving constantly. The recent development [20] of a membrane permeant, caged protonophore (2,4-dinitrophenol), which has been targeted to the matrix of the mitochondrion by an alkyltriphenylphosphonium lipophilic cation and releases the locally in predetermined regions in response to directed irradiation with UV light via a local photolysis system, will improve understanding of the mitochondrial control of local and global Ca 2+ signals in smooth muscle.…”
Section: Discussionmentioning
confidence: 99%